Identification of cavotricuspid isthmus voltage patterns in typical atrial flutter ablation - Francisco Ribes; Ángel Ferrero‐de‐Loma‐Osorio; Juan Miguel Sánchez‐Gómez; Lourdes Bondanza; Ángel Martínez‐Brotons; Ricardo Ruiz‐Granell (Journal of Arrhythmia, 2024)
Abstract Background Electroanatomical mapping is an essential tool in the ablation of typical AFL. Objectives To identify the existence of voltage patterns in the CTI voltage maps and their relevance for typical AFL ablation. Methods A voltage map of the CTI was made prior to ablation, identifying the areas of maximum voltage and their location along the CTI, allowing classification into patterns according to their distribution. A stepwise ablation approach targeting the areas of maximum voltage was conducted. The ablation characteristics were compared based on the pattern obtained. Results Two voltage patterns were identified, with differences in ablation time to bidirectional CTI block. No complications occurred. Conclusions Voltage mapping identifies patterns in the CTI with implications for typical AFL ablation.